Overweight and obesity in shift workers: associated dietary and lifestyle factors. (27th May 2020) - O'Brien, Victoria M; Nea, Fiona M; Pourshahidi, L Kirsty; Livingstone, M Barbara E; Bardon, Laura; Kelly, Ciara; Kearney, John M; Corish, Clare A
Abstract: Background: Approximately 17% of the European Union workforce is engaged in shift work. Shift work has been associated with a number of chronic conditions, including obesity and obesity-related metabolic diseases. The aim of this study was to explore the dietary and lifestyle behaviours of shift workers with a healthy vs. overweight/obese body mass index (BMI). Methods: A cross-sectional study was conducted on 1080 shift workers using a 15-min, telephone-administered questionnaire developed from qualitative research on Irish shift workers and national dietary intake data. Demographic and work-related factors, as well as dietary and lifestyle behaviours were recorded. BMI was calculated using self-reported height and weight. Univariate and multivariate logistic regression methods were used to analyze data according to BMI category. Results: Over 40% of shift workers were classified as overweight or obese. Multivariate analysis indicated that being male [ P < 0.001, aOR = 2.102, 95% CI (1.62–2.73)] and middle- or older-aged were independently associated with overweight and obesity [ P < 0.001, aOR = 2.44 95% CI (1.84–3.24) and P < 0.001, aOR = 2.9 95% CI (1.94–4.35), respectively]. Having a medium–high consumption of fried foods was independently associated with overweight and obesity [aOR = 1.38, 95% CI (1.06–1.8)]. Conclusions: Similar to the general population, overweight and obesity were strongly associated with male sex and middle- or older-age. Male shift workers may benefit from targeted dietary and lifestyle advice specifically focused on limiting fried foods to help protect against overweight and obesity.